2015
DOI: 10.1186/s12871-015-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation to support repeated whole-lung lavage in a patient with pulmonary alveolar proteinosis in life threatening dyspnoe – a case report

Abstract: BackgroudPulmonary alveolar proteinosis is a rare disorder that is characterized by a large accumulation of lipoproteinaceous material within the alveoli. This causes respiratory failure due to a restriction of gas exchange and changes in the ventilation/perfusion ratio. Clinical symptoms are variable and depend on the severity of damage of the lung parenchyma. Treatment method is whole-lung lavage, where the accumulated lipoproteinaceous material is removed using large quantities of saline.Case presentationTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…It announced that PAP patients who have bad general status, need of ventilation, have good results with extracorporeal membrane oxygenation (ECMO) support lung lavage [15]. However, our center has not ECMO background so we could not support the patient with ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…It announced that PAP patients who have bad general status, need of ventilation, have good results with extracorporeal membrane oxygenation (ECMO) support lung lavage [15]. However, our center has not ECMO background so we could not support the patient with ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Formas severas de proteinosis alveolar, aunque bien descriptas, son infrecuentes 3 . El LPT ha sido bien descripto bajo soporte vital con circulación extracorpórea y más recientemente ECMO 2,5,6 . La decisión de realizar LPT bajo ECMO veno-venoso en lugar de venoarterial puede ser controversial por el potencial fallo del ventrículo derecho, pero en este caso fue bien tolerado.…”
Section: Discussionunclassified
“… 3 , 4 , 11 ECMO is not able to reverse the poor prognosis in patients who do not qualify for lung transplantation. 11 , 12 Chiumello et al referred, that the report by the United Network of Organ Sharing showed that, despite its complexity and side effects, the use of ECMO as a bridge to lung transplantation has risen by 150% in the last 2 years compared to the previous decades (1970–2010). 3 ECMO is an alternative, rather than an adjunct, to invasive mechanical ventilation and is a better bridging strategy to lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“… 3 ECMO is an alternative, rather than an adjunct, to invasive mechanical ventilation and is a better bridging strategy to lung transplantation. 2 , 11 , 12 Extra-corporeal life support as a bridge to lung transplantation is a promising option for patients with end-stage lung disease on the organ transplant waiting list. 13 The shear stress created by the mechanical pumps causes changes in the hemocoagulation system in almost all patients treated with ECMO.…”
Section: Discussionmentioning
confidence: 99%